2020
DOI: 10.3389/fimmu.2020.01511
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Peptides and Ectosymbiotic Relationships: Involvement of a Novel Type IIa Crustin in the Life Cycle of a Deep-Sea Vent Shrimp

Abstract: The symbiotic shrimp Rimicaris exoculata dominates the macrofauna inhabiting the active smokers of the deep-sea mid Atlantic ridge vent fields. We investigated the nature of the host mechanisms controlling the vital and highly specialized ectosymbiotic community confined into its cephalothoracic cavity. R. exoculata belongs to the Pleocyemata, crustacean brooding eggs, usually producing Type I crustins. Unexpectedly, a novel anti-Gram-positive type II crustin was molecularly identified in R. exoculata. Re-crus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 70 publications
1
19
1
Order By: Relevance
“…It is interesting that, based on its cysteine-rich region [ 30 ], Crus1 was classified by phylogenetic analysis as a member of the Type I crustin, which has been mainly found in crabs and lobsters [ 31 ]. This observation of Crus1 is in contrast to that of the recently reported Re-crustin from the hydrothermal vent in MAR, which is a Type II crustin [ 27 ] and, as shown in our study, shares a low sequence identity with Crus1. These results suggest the possible existence of diverse forms of crustins in deep sea hydrothermal shrimp.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…It is interesting that, based on its cysteine-rich region [ 30 ], Crus1 was classified by phylogenetic analysis as a member of the Type I crustin, which has been mainly found in crabs and lobsters [ 31 ]. This observation of Crus1 is in contrast to that of the recently reported Re-crustin from the hydrothermal vent in MAR, which is a Type II crustin [ 27 ] and, as shown in our study, shares a low sequence identity with Crus1. These results suggest the possible existence of diverse forms of crustins in deep sea hydrothermal shrimp.…”
Section: Discussioncontrasting
confidence: 99%
“…MT375562). The sequence identity between Crus1 and Re-crustin, the Type II crustin identified in the shrimp from MAR [ 27 ], is 24.74%. The sequence alignment between Crus1 and representative Type I crustins indicated that the conserved WAP domain, in particular the 8 cysteines that form the four-disulfide core structure, was shared among the crustins ( Figure 1 A).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Anti-fungal activity was also demonstrated for Rsp ALF1. Le Bloa et al (2020) identified an AMP in R. exoculata, which they named Recrustin. Re-crustin is mainly synthesized in the tissues on which the ectosymbiotic community of the branchial chamber develops, i.e.…”
Section: Pathogen Recognition and Non-proliferation Of Symbiontsmentioning
confidence: 99%
“…the branchiostegite and scaphognathite. As it is mostly expressed at the juvenile stage, Re-crustin has been proposed to be involved in symbiont attraction and adhesion (Le Bloa et al 2020). AMPs could thus also play a role in host symbiont recognition and not just in the regulation of their proliferation.…”
Section: Pathogen Recognition and Non-proliferation Of Symbiontsmentioning
confidence: 99%